Reformulasi Sanksi Pidana pada Tindak Pidana Korupsi yang Merugikan Keuangan Negara - Aditya Wiguna Sanjaya; Muhammad Hoiru Nail (Fakultas Hukum Universitas Islam Jember, 2026)
The purpose of this study is to examine and analyze whether the regulation of criminal sanctions for corruption offenses related to state financial losses, as stipulated in Articles 603 and 604 of the Criminal Code, is consistent with the principles of justice. It also aims to explore and formulate an ideal framework for regulating criminal sanctions for corruption offenses involving state financial losses in the future. This research employs a normative legal research method, utilizing both the statute approach and the conceptual approach. The findings of this study indicate that the current regulation of criminal sanctions for corruption offenses related to state financial losses does not yet reflect the values of justice. Furthermore, the ideal formulation of criminal sanctions, as provided in Article 604 of the Criminal Code, needs to be reformulated so that the severity of its sanctions becomes greater than those prescribed under Article 603 of the Criminal Code